The Effect of Biologics in the Treatment of Multisystem Inflammatory Syndrome in Children (Mis-C): A Single-Center Propensity-Score-Matched Study - Ozge Basaran; Ezgi Deniz Batu; Ummusen Kaya Akca; Erdal Atalay; Muserref Kasap Cuceoglu; Seher Sener; Zeynep Balık; Erdem Karabulut; Selman Kesici; Tevfik Karagoz; Yasemin Ozsurekci; Yelda Bilginer; et al. (MDPI AG, 2023)
Multisystem inflammatory syndrome in children (MIS-C) is a serious condition characterized by excessive inflammation that can arise as a complication of SARS-CoV-2 infection in children. While our understanding of COVID-19 and MIS-C has been advancing, there is still uncertainty regarding the optimal treatment for MIS-C. In this study, we aimed to compare the clinical and laboratory outcomes of MIS-C patients treated with IVIG plus corticosteroids (CS) to those treated with IVIG plus CS and an additional biologic drug. We used the propensity score (PS)-matching method to assess the relationships between initial treatment and outcomes. The primary outcome was a left ventricular ejection fraction of less than 55% on day 2 or beyond and/or the requirement of inotrope support on day 2 or beyond. We included 79 MIS-C patients (median age 8.51 years, 33 boys) followed in our center. Among them, 50 children (25 in each group) were allocated to the PS-matched cohort sample. The primary outcome was observed in none of the patients in the IVIG and CS group, while it occurred in eight patients in the IVIG plus CS and biologic group (p = 0.04). MIS-C is a disorder that may progress rapidly and calls for extensive care. For definitive recommendations, further studies, including randomized control trials, are required.